COVID-19 and Psychopathologies in Children-A Single Session Intervention Plan to Promote Mental Health during Crises Management : A Systematic Review - Sana, Rehman; Siti Raudzah, Ghazali; Ask, Elklit (Tehran University of Medical Sciences (TUMS) Journals Publishing House, 2025)
Background: The world has experienced numerous natural and man-made disasters throughout history. Due to these unforeseen circumstances, children and adolescents have reported significant psychopathologies in response to traumatic experiences. We aimed to investigate the surge of internalizing and externalizing psychopathologies during COVID-19 and to assess the efficacy of single-session therapies used to treat mental health issues during this period. Methods: Overall, 270 articles were retrieved across both phases of the study, with 250 articles identified in Phase I and 20 in Phase II. Following the PRISMA flowchart guidelines, approximately 30 studies were selected to meet the objective of Phase I, while 10 studies were chosen to address the objective of Phase II. The articles were retrieved from various databases, including PubMed, Google Scholar, Scopus, Ovid, CENTRAL, JSTOR, NCBI, and Science Direct. Only articles published between 2019 and 2022 were included in the study. Results: The findings of first phase of study indicated a surge in internalizing psychopathologies (such as anxiety, depression, loneliness, and somatic problems) and externalizing psychopathologies (including conduct/oppositional disorders, sleep disturbances, suicidal ideation, ADHD, and substance abuse) over the past four years. Additionally, according to the findings of the second phase of the study, single-session therapies were found to be effective in mitigating symptoms of depression and anxiety. Conclusion: The study's findings are discussed in the context of counseling adolescents, highlighting the importance of addressing mental health issues in this demographic.